PUBLIC PERCEPTION OF MASS MEDIA AWARENESS CREATION OF THE IMPLICATIONS OF NIGERIA’S TAX REFORM BILLS, 2024 - Adejoh , Monday; Jibrin , Umar Omachi (Top Journal of Public Policy and Administration (TJPPA), 2025)
This study examined the public perception mass media awareness creation and the implications of the 2024 tax reform Bills. It had three objectives such as; appraise the degree of public exposure to mass media awareness creation regarding the implications of the 2024 tax reform bills examine mass media channels through which the public access information regarding the implications of the tax reform bill 2024 and investigate public perception of the media awareness creation regarding the implications of the tax reform bill 2024. The study adopted the Social Responsibility Media Theory as its theoretical foundation. It adopted a qualitative survey method using a questionnaire for data collection. It found that 54% of the respondents agreed to be highly exposed to the mass media awareness creation of the implications of the 2024 Tax Reform Bills, 63% of the respondents agreed that the social media platforms were the channels through which they got information about the new Tax Reform Bills, 2024 and finally, the respondents agreed that the mass media awareness creation was highly effective. with 53% of the respondents in congruence with the assertion. It concluded that the awareness creation of Mass media was impressive and recommended that journalists should be professional and continue to effectively discharge their social responsibility media theory to the public